Tanshinol Alleviates Microcirculation Disturbance and Impaired Bone Formation by Attenuating TXNIP Signaling in GIO Rats - Lai, Wenxiu; Mo, Yulin; Wang, Dongtao; Zhong, Ying; Lu, Lujiao; Wang, Jiajia; Cui, Liao; Liu, Yanzhi; Yang, Yajun (Frontiers in Pharmacology, 2021)
Impaired bone formation is the main characteristics of glucocorticoid (GC)-induced osteoporosis (GIO), which can be ameliorated by tanshinol, an aqueous polyphenol isolated from Salvia miltiorrhiza Bunge. However, the underlying mechanism is still not entirely clear. In the present study, we determined the parameters related to microstructure and function of bone tissue, bone microcirculation, and TXNIP signaling to investigate the beneficial effects of tanshinol on skeleton and its molecular mechanism in GIO rats. Male Sprague-Dawley rats aged 4 months were administrated orally with distilled water (Con), tanshinol (Tan, 25 mg•kg-1•d-1), prednisone (GC, 5 mg•kg-1•d-1) and GC plus tanshinol (GC + Tan) for 14 weeks. The results demonstrated that tanshinol played a significant preventive role in bone loss, impaired microstructure, dysfunction of bone metabolism and poor bone quality, based on analysis of correlative parameters acquired from the measurement by using Micro-CT, histomorphometry, ELISA and biomechanical assay. Tanshinol also showed a significant protective effect in bone microcirculation according to the evidence of microvascular perfusion imaging of cancellous bone in GIO rats, as well as the migration ability of human endothelial cells (EA.hy926, EA cells). Moreover, tanshinol also attenuated GC-elicited the activation of TXNIP signaling pathway, and simultaneously reversed the down-regulation of Wnt and VEGF pathway as manifested by using Western-blot method in GIO rats, EA cells, and human osteoblast-like MG63 cells (MG cells). Collectively, our data highlighted that tanshinol ameliorated poor bone health mediated by activation of TXNIP signaling via inhibiting microcirculation disturbance and the following impaired bone formation in GIO rats.